Al-Maṣārif al-Islāmiyah wa al-qānūn al-Maṣrāfī fī indūnīsīyā - Syamsul Anwar (Al-Jami'ah Research Centre, 2001)
This paper examines the development of syariah banking in Indonesia and the law governing the activities of such banking. It is divided into three sections, i.e. introduction, main topics and Arabic translation of some chapters of Indonesian law of Banking (Code number 7/1992 and its revition, code number 10/1988) as well as decree of Indonesian Bank Director about Conventional Bank Based on Syariah Principles. In this paper, the writer elaborates the development of ideas for establishing syariah banking system. This kind of banking had actually been developed in 1970’s. however, these banks dissolved by themselves.in 1991, two Islamic “small” banks, Dana Matdhatilla and Amal Sejahtera, has been established; and in 1992, general syariah Bank, Bank Muamalat Indonesia, has also been established. The writer then explains about the development of syariah banking system in Indonesia afterwards. Almost a decade up to august 2001, there are only 5 general syariah Banks and 81 ‘small” syariah Banks with total amount of asset and money less than 1 % of that of conventional Banks in Indonesia. This indicates the slow development of syariah banking in Indonesia compared to that of Middle East where are many Islamic banks that become high level of bank in only a decade. This slow is caused by, partly, the concept of Islamic banking is relatively new in Indonesia so that it has hardly ever been known by Indonesian community. It is also because of the lack of human and financial resources, and that of regulation especially before the revision of Code number 7/1992. In the third section of this paper, the writer explains about the law that becomes the basis of syariah banking activities. In this section, it is explained about banking structure as well as variety of business and banking ownership. It is also explained handicaps faced by syariah banking in which further legal regulation is needed.